Day 4 Wed, December 01, 2021 2021
DOI: 10.2118/204707-ms
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Microservice for Identification of Accident Predecessors

Abstract: Drilling accidents prediction is the important task in well construction. Drilling support software allows observing the drilling parameters for multiple wells at the same time and artificial intelligence helps detecting the drilling accident predecessor ahead the emergency situation. We present machine learning (ML) algorithm for prediction of such accidents as stuck, mud loss, fluid show, washout, break of drill string and shale collar. The model for forecasting the drilling accidents is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Step 4. Plot the highlighted 𝜏 segments and accident probabilities Figure 2: General scheme for interpretation of Bag-of-features model, used for drilling accident forecasting problem (Gurina et al, 2022b(Gurina et al, , 2021.…”
Section: Methodology For Bag-of-features Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…Step 4. Plot the highlighted 𝜏 segments and accident probabilities Figure 2: General scheme for interpretation of Bag-of-features model, used for drilling accident forecasting problem (Gurina et al, 2022b(Gurina et al, , 2021.…”
Section: Methodology For Bag-of-features Interpretationmentioning
confidence: 99%
“…Since the current study is mostly aimed at studying the interpretability techniques for black-box machine learning models, in this section we describe methods that are used nowadays to interpret forecasting black-box models and assess the quality of obtained interpretability. The full literature review related to the forecasting of drilling accidents can be found in papers (Gurina et al, 2021(Gurina et al, , 2022b, while here we mostly focus on the review of the system that provides forecast and explanation why it was made.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations